The Homosexual Marriage: An Interdisciplinary Vision - Gutiérrez Velasco, Flavio (2020)
This paper addresses gay marriage in the 21st century, from an interdisciplinary perspective, from a holistic perspective. In the sociocultural sphere this is a reality that cannot be ignored; Legally, it has been elevated to the status of marriage in many laws; in the anthropological there are conceptions for and against; and on the religious level it is approached from the vision of the Catholic Church and the Church of Jesus Christ of Latter-day Saints.